Molecular and Biological Characterisation of Human Skin Dermal Pericytes - Pieterse-Mulley, Zalitha (Curtin University, 2023)
This study explored the characteristics of human skin pericytes and their role in skin regeneration. Zalitha demonstrated that pericytes can support the regeneration of skin and identified three novel and distinct types of pericyte with distinct locations in the skin contributing to their function. The findings of this study will improve patient outcomes for burns and wound healing.